Ceramic filter tube as well as preparation method and application thereof
By using the method of integrated molding of the foam nickel-supported skeleton and the ceramic filter tube matrix in the ceramic filter tube, the problem of pipe breakage caused by insufficient strength and incompatibility of the reinforcement structure of the ceramic filter tube is solved, and the seismic resistance and service life are achieved, and the catalytic performance is improved.
Patent Information
- Application Number
- CN202510007667.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-03-21
AI Technical Summary
Due to insufficient strength, ceramic filter pipes are prone to break under external forces, resulting in shortening of service life. The existing reinforcement structures are incompatible due to material differences, resulting in structure separation and falling off, resulting in pipe breakage problems.
The nickel foam support frame is used as the reinforcement structure of the ceramic filter tube. The ceramic filter tube matrix is integrally formed on the two-sided surface of the nickel foam support frame to prevent the reinforcement structure from being separated and fall off from the ceramic filter tube.
It improves the seismic resistance and service life of ceramic filter tubes, reduces the possibility of tube breaking, and improves the catalytic performance of the catalyst.
Smart Images

Figure CN119656738A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of waste gas treatment and relates to a ceramic filter tube and a preparation method and application thereof. Background Art
[0002] With the increasing development of modern industrial technology, the harm caused by polluting flue gas generated in the process of energy utilization to the ecological environment and human life has become an issue that cannot be ignored. Taking heavy pollution industries such as power plants and heating boilers as an example, the flue gas generated by the combustion of fuels such as coal tar, natural gas, petroleum coke powder and even raw coal in boilers or kilns mainly includes dust, sulfur oxides, nitrogen oxides and other harmful substances. If it is directly discharged into the air, it will not only pollute the ecological environment and endanger human health, but also corrode production equipment and have an adverse effect on the entire production process. The main ways to purify sulfur oxides and nitrogen oxides in boiler flue gas are denitration and desulfurization before combustion, denitration and desulfurization during combustion, and denitration and desulfurization after combustion. Denitration and desulfurization after combustion is flue gas denitration and desulfurization.
[0003] At present, ceramic filter tubes have become the preferred carrier for the coordinated purification of multiple pollutants such as saltpeter and dust due to their good dust retention rate, thermal stability, chemical stability, cleaning resistance, long service life, small footprint, easy installation and convenient maintenance.
[0004] However, with the application of ceramic filter tubes, the problems of filter tubes have also become prominent. Due to the complex and changeable flue gas conditions, higher requirements are placed on the inherent strength of ceramic filter tubes. Since the ceramic filter tubes themselves are highly brittle and the ceramic fiber filter tubes have the characteristics of high porosity, their strength is relatively low. They may break and disintegrate at the clamping end or other force-bearing end when subjected to external forces, causing inconvenience in use. They must be replaced frequently, which increases the cost of use. Therefore, the strength of the ceramic filter tube has an important impact on its service life. Insufficient strength can easily cause damage and breakage during continuous operation, shortening its service life. Among the existing literature on improving the strength of ceramic filter tubes, CN105107310A discloses a catalytic ceramic filter tube and a preparation method. The ceramic filter tube includes a ceramic filter tube substrate, and a catalytically active component layer and a separation membrane sequentially coated on the ceramic filter tube substrate. CN107398133A uses silica sol to strengthen the head and tail of the ceramic filter tube to solve the problem of the existing ceramic filter tube, but does not consider the problem of tube breakage caused by insufficient tube body strength; CN112704978A uses rigid material or flexible mesh material compounded on the outer surface or inner surface of the filter tube as a reinforcement structure of the filter tube, and as a protective net after the ceramic filter tube breaks to prevent the ceramic filter tube from falling into the ash hopper of the dust removal equipment after the ceramic filter tube breaks, but does not consider the compatibility and bonding performance of the thermal expansion coefficient of the rigid material or flexible mesh material and the ceramic filter tube substrate under high temperature application, resulting in the separation and fall-off of the reinforcement structure and the ceramic filter tube substrate, resulting in tube breakage.
[0005] Therefore, how to solve the compatibility of various structures in the ceramic filter tube, avoid the problem of tube breakage caused by structural separation and falling off, and improve the seismic performance and service life of the ceramic filter tube is a technical problem that needs to be solved urgently. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a ceramic filter tube and its preparation method and use. The ceramic filter tube provided by the present invention uses a nickel foam support frame as the reinforcement structure of the ceramic filter tube, and the ceramic filter tube matrix is integrally formed on the double-side surfaces of the nickel foam support frame, which fundamentally solves the incompatibility of the current reinforcement structure caused by material differences, avoids the problem of tube breakage caused by the separation and detachment of the reinforcement structure and the ceramic filter tube, reduces the possibility of tube breakage of the ceramic filter tube during the use of high-temperature flue gas, improves the seismic resistance and service life of the ceramic filter tube; and also improves the catalytic performance of the catalyst.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a ceramic filter tube, the ceramic filter tube comprising:
[0009] Nickel foam support frame;
[0010] A ceramic filter tube matrix, wherein the ceramic filter tube matrix is integrally formed on both side surfaces of the nickel foam support frame;
[0011] Catalyst, the catalyst is loaded in the pores of the ceramic filter tube matrix and in the nickel foam support skeleton.
[0012] The ceramic filter tube provided by the present invention uses nickel foam as a supporting skeleton, and the ceramic filter tube matrix is integrally formed on the double-side surfaces of the nickel foam supporting skeleton. Under the premise of ensuring the original performance of the ceramic filter tube, the strength of the ceramic filter tube can be improved, fundamentally solving the incompatibility of the current reinforcement structure caused by material differences, avoiding the problem of tube breakage caused by the separation and falling of the reinforcement structure from the ceramic filter tube, and improving the seismic resistance and service life of the ceramic filter tube; in addition, the nickel foam can also be used as a secondary supplementary reinforcement carrier for the catalyst, which has the advantages of stabilizing the catalyst and further enhancing its denitrification performance.
[0013] In the present invention, the ceramic filter tube matrix and the nickel foam are formed in one piece to avoid the problem of tube breakage caused by the separation and fall-off of the reinforcement structure from the ceramic filter tube; if the ceramic filter tube matrix is only located on one side of the nickel foam support frame, that is, the nickel foam is not located inside the ceramic filter tube matrix structure but is exposed to the outside, the problem of tube breakage due to insufficient strength of the ceramic filter tube during use cannot be solved. Since the ceramic filter tube is used in high-temperature dusty flue gas, the high-temperature flue gas continuously flushes the ceramic filter tube, and the nickel foam on the outside of the ceramic filter tube matrix is easily separated from the matrix material by the flushing of the flue gas, losing its integrity, resulting in a decrease in the overall strength of the ceramic filter tube and causing tube breakage; in addition, due to the difference in thermal expansion coefficients between the ceramic filter tube substrate and the nickel foam, the nickel foam on the outside is more easily separated from the substrate.
[0014] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0015] Preferably, the wall thickness of the nickel foam support skeleton is 2 to 5 mm, for example, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm or 5 mm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0016] In the present invention, the wall thickness of the nickel foam support skeleton is adjusted to 2-5 mm, which ensures that the ceramic filter tube has a higher overall strength and avoids the problem of tube breakage.
[0017] Preferably, the pore size of the nickel foam support skeleton is 3 to 6 mm, for example, 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm, 5.5 mm or 6 mm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] Preferably, the porosity of the nickel foam skeleton is 90% to 96%, for example, 90%, 91%, 92%, 93%, 94%, 95% or 96%.
[0019] Due to the irregular interweaving and compounding between fibers during the vacuum forming process of the ceramic fiber substrate to form special three-dimensional interconnected stepped filtration pores, the ceramic filter tube mainly functions to intercept dust or other pollutant particles. It is a wall-flow filtration mechanism, and its filtration performance is greatly affected by the porosity of the matrix. The porosity of conventional ceramic filter tubes is generally 70-90%, while the present invention further adjusts the porosity to 90%-96%, thereby ensuring a high porosity of the ceramic filter tube and achieving a good filtration effect. In addition, the high-porosity nickel foam can increase the interweaving contact area of the ceramic fibers on both sides of the nickel foam, thereby improving the integrity of the filter tube and improving the overall strength and seismic resistance of the filter tube.
[0020] Preferably, the nickel foam support skeleton comprises modified nickel foam, and the modified nickel foam comprises nickel foam and an inorganic binder for modifying the surface of the nickel foam.
[0021] In the present invention, modified nickel foam is selected as the supporting skeleton, which improves the adhesion between the nickel foam and the ceramic matrix material, better realizes the combination of the two, and improves the compatibility of the nickel foam and the ceramic filter tube substrate, thereby ensuring that the reinforcing material modified nickel foam and ceramic fiber are not separated due to the thermal expansion rate of the materials under high-temperature use conditions, thereby ensuring the overall strength of the ceramic filter tube, and the seismic resistance and service life are better; and the modified nickel foam can also be used as a secondary supplementary reinforcement carrier for the denitration catalyst, which has the advantages of stabilizing the catalyst and further enhancing its denitration performance.
[0022] Furthermore, organic binders can be used to modify nickel foam. However, compared with inorganic binders, organic binders have the problem of weakening overall strength in the later stage. The organic structure of organic binders is easily destroyed in a high temperature environment, causing the binder to fail, thereby destroying the original structure of the ceramic filter tube, causing strength reduction or even tube breakage. Therefore, the use of inorganic binders will neither affect the performance of the ceramic filter tube itself nor cause the problem of the binder being destroyed due to high temperature.
[0023] Preferably, the inorganic binder includes an aluminum-containing binder and / or a silicon-containing binder.
[0024] When the type of the inorganic binder in the present invention is consistent with at least one material image of the ceramic material in the ceramic filter tube substrate, the ceramic filter tube substrate and the nickel foam can be better firmly bonded.
[0025] Preferably, the ceramic filter tube is a cylindrical ceramic filter tube.
[0026] Preferably, the ceramic filter tube matrix comprises a ceramic fiber filter tube matrix.
[0027] In the present invention, ceramic fiber is used as the raw material of the ceramic filter tube matrix. The ceramic fiber has the advantages of light weight, high temperature resistance, corrosion resistance, good thermal stability, not easy to produce chemical reactions and resistance to mechanical vibration. The main component is Al2O3, which has a porous structure and can be used as a secondary carrier of the catalyst. After molding, it is more conducive to forming special three-dimensional interconnected ladder filtration pores, which is particularly suitable for application materials in the field of high-temperature flue gas filtration. The specific material types of ceramic fibers are all selected by conventional technology. Those skilled in the art can make adaptive choices based on actual needs. For example, the ceramic fibers include but are not limited to aluminum silicate fibers, polycrystalline fibers, etc.
[0028] Preferably, taking the central axis of the tube wall of the ceramic filter tube as the x-axis, along the direction perpendicular to the x-axis, the distance a between the position of the nickel foam support skeleton and the x-axis is 0 to 1 / 10t, for example, 0.01t, 0.02t, 0.03t, 0.04t, 0.05t, 0.06t, 0.07t, 0.08t, 0.09t or 0.1t, etc., wherein the wall thickness of the tube wall is t, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] It should be noted that the central axis of the tube wall of the ceramic filter tube in the present invention generally refers to the center line of the tube wall thickness, which is located at the midpoint between the inner wall and the outer wall of the pipe; for a circular pipe with uniform wall thickness, the central axis of the tube wall is an imaginary line that divides the thickness of the tube wall into two equal parts, from the inner wall to the outer wall, and this line passes through the geometric center of the tube wall.
[0030] In the present invention, the nickel foam support skeleton is located at the central axis of the ceramic filter tube wall, and the effect is the best. Inevitably, there will be a certain offset distance a. If a is too large, that is, the offset degree of the nickel foam support skeleton is too high, it will seriously affect the service life of the ceramic filter tube. If the offset distance a is too large, the wall thickness on one side of the support skeleton will be thinner. Under high-temperature use conditions, the ceramic filter tube may be continuously washed away by smoke and dust, causing the thin filter tube wall on one side to separate from the nickel foam and fall off, seriously affecting the overall strength and service life of the filter tube, and even causing the filter tube to break and be scrapped.
[0031] Preferably, the catalyst comprises a denitration catalyst.
[0032] In the present invention, in addition to the denitration catalyst, a catalyst for removing non-methane total hydrocarbons may be added, and those skilled in the art may make adaptive selection and adjustment according to actual needs.
[0033] Furthermore, the present invention does not specifically limit the specific types of denitration catalysts and denitration catalysts for non-methane hydrocarbons. The present invention is applicable to any conventional denitration catalyst or denitration catalyst for ceramic filter tubes that can be known to those skilled in the art within a reasonable range. For example, the denitration catalyst includes but is not limited to at least one of vanadium oxide, tungsten oxide, molybdenum oxide, and oxides of precious metals or rare earth elements (such as nano vanadium tungsten titanium catalyst), and the denitration catalyst for non-methane hydrocarbons includes but is not limited to platinum catalysts, etc.
[0034] In a second aspect, the present invention provides a method for preparing the ceramic filter tube according to the first aspect, the preparation method comprising the following steps:
[0035] Compounding the ceramic filter tube matrix slurry on the surface of the nickel foam, forming, and loading the catalyst to obtain the ceramic filter tube;
[0036] Wherein, the shape of the nickel foam is the shape of the ceramic filter tube.
[0037] In the present invention, the catalyst loading method is a conventional technical means, including but not limited to vacuum impregnation method, quantitative spraying method or reciprocating coating method, etc., and those skilled in the art can make adaptive selection and adjustment according to actual needs.
[0038] The preparation method provided by the present invention realizes the simultaneous arrangement of a ceramic filter tube matrix on both side surfaces of foamed nickel through a ceramic filter tube slurry composite method. After a molding process, an integrally formed composite structure of the ceramic filter tube matrix and foamed nickel is obtained. After a catalyst is loaded in the composite structure, a ceramic filter tube with high strength and excellent catalytic performance is obtained.
[0039] Preferably, the nickel foam comprises modified nickel foam, and the preparation method of the modified nickel foam comprises:
[0040] The nickel foam to be modified is subjected to an erosion treatment, and then immersed in a modifier solution for a modification treatment to obtain a modified nickel foam.
[0041] In the present invention, after the modified nickel foam is corroded, rough sites are formed on the surface of the nickel foam, which increases the contact area of the modifier and ensures the close combination of the modifier on the surface of the nickel foam.
[0042] Preferably, the diameter d of the nickel foam, the diameter D of the ceramic filter tube and the wall thickness t of the ceramic filter tube satisfy: d=D-1 / 2t.
[0043] Preferably, the nickel foam to be modified is cleaned and then subjected to corrosion treatment.
[0044] In the present invention, the oily substance in the nickel foam is removed by washing the nickel foam; the specific washing process includes sequentially performing alkali washing and water washing, wherein the alkali washing removes the oily substance, and further performing water washing removes the alkaline substance remaining in the nickel foam, and the alkaline substance in the alkaline washing solution (the concentration can be 0.1 to 1 mol / L) includes but is not limited to at least one of sodium hydroxide, potassium hydroxide, sodium carbonate or sodium bicarbonate.
[0045] Preferably, the etching liquid of the etching treatment comprises an acid solution.
[0046] The present invention does not impose any particular limitation on the type of acid used in the acid solution. Conventional types of acids that can be used for roughening treatment are applicable to the present invention, such as hydrochloric acid and / or sulfuric acid.
[0047] Preferably, the concentration of the acid solution is 1-5 mol / L, such as 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L or 5 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0048] In the present invention, after the etching treatment, water washing may be performed again to remove the residual etching solution.
[0049] Preferably, the modifier solution comprises a salt solution containing an inorganic binder.
[0050] In the present invention, the specific substance type in the salt solution and at least one inorganic element of the main ceramic material in the ceramic filter tube substrate remain consistent; if the ceramic material includes silicon and aluminum elements, an aluminum nitrate solution containing an inorganic binder can be selected.
[0051] Preferably, the concentration of the modifier solution is 0.1-2 mol / L, such as 0.1 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L or 2 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] Preferably, the inorganic binder is added in an amount of 5 to 10 wt % of the weight of the salt in the salt solution, for example 5 wt %, 5.5 wt %, 6 wt %, 6.5 wt %, 7 wt %, 7.5 wt %, 8 wt %, 8.5 wt %, 9 wt %, 9.5 wt % or 10 wt %, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] In the present invention, by further adjusting the concentration of the modifier solution to 0.1-2 mol / L and / or the amount of the inorganic binder added to 5-10 wt% of the weight of the salt in the salt solution, it is more conducive to improving the dispersion of the modifier in the nickel foam and ensuring that the modifier is evenly dispersed and attached on the surface of the nickel foam; if the concentration of the modifier is too high, the modifier will accumulate on the surface of the nickel foam, resulting in material waste and being unfavorable for the dispersion of the modifier.
[0054] Preferably, the modification treatment comprises sequentially performing a first drying and a heat treatment.
[0055] Preferably, the temperature of the heat treatment is 300-400°C, for example 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C or 400°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] Preferably, the heat treatment time is 3 to 6 hours, such as 3 hours, 4 hours, 5 hours or 6 hours, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0057] Preferably, the molding method includes vacuum filtration molding.
[0058] Preferably, the formed embryo body is subjected to a second drying treatment.
[0059] Preferably, the method of loading the catalyst comprises a catalyst slurry coating method.
[0060] In the present invention, the coating amount of the catalyst slurry is a conventional technical solution, and the specific coating amount is regulated based on the weight of the pure catalyst, which accounts for 5wt% to 15wt% of the total weight of the ceramic filter tube, for example, 5wt%, 6wt%, 7wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 7wt% to 11wt%.
[0061] The appropriate amount of catalyst coating is an important factor in ensuring the catalytic performance and dust removal performance of the filter tube. A low coating amount will result in insufficient catalytic performance, while a high coating amount will cause excessive pressure difference in the ceramic filter tube and affect the dust removal performance of the ceramic filter tube.
[0062] As a preferred technical solution, the preparation method comprises the following steps:
[0063] The nickel foam to be modified is cleaned, and after cleaning, it is corroded in an acid solution with a concentration of 1 to 5 mol / L, and then immersed in a salt solution containing an inorganic binder with a concentration of 0.1 to 2 mol / L, first dried, and after the first drying, heat treated at 300 to 400° C. for 3 to 6 hours to obtain a modified nickel foam;
[0064] Compounding the ceramic filter tube matrix slurry on the surface of the nickel foam, vacuum filtering and forming, performing a second drying process on the embryo after vacuum filtering and forming, and loading the catalyst by a catalyst slurry coating method to obtain the ceramic filter tube;
[0065] Wherein, the added amount of the inorganic binder is 5-10wt% of the weight of the salt in the salt solution.
[0066] It should be noted that, in the preparation process of the ceramic filter tube of the present invention, except for the above-mentioned characteristic limitations, the rest of the raw material preparation and preparation process are all conventional technical solutions.
[0067] Optionally, the solid content of the ceramic substrate slurry is 5wt% to 12wt%, for example, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt% or 12wt%, and the viscosity is 3 to 20mPa.s, for example, 3mPa.s, 5mPa.s, 10mPa.s, 15mPa.s or 20mPa.s, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0068] The ceramic substrate slurry includes a ceramic substrate raw material, an inorganic binder, an organic binder and water; the mass ratio of the ceramic substrate raw material, the inorganic binder and the organic binder is (15-30):2:1, for example, 15:2:1, 20:2:1, 25:2:1 or 30:2:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0069] Optionally, the composite method comprises a slurry injection method.
[0070] Optionally, the viscosity of the catalyst slurry is 3 to 20 mPa.s, for example, 3 mPa.s, 5 mPa.s, 8 mPa.s, 10 mPa.s, 13 mPa.s, 15 mPa.s, 18 mPa.s, 20 mPa.s, 23 mPa.s, 25 mPa.s, 28 mPa.s or 30 mPa.s, etc.; the catalyst slurry includes a catalyst and water, and the particle size of the catalyst is smaller than the pore size of the ceramic filter tube, and the average particle size is not greater than 500 nm; since the pores of the ceramic filter tube are in the micron level, in order for the catalyst slurry to pass through the pores of several microns and be coated into and evenly distributed on the intricate and irregular microporous structure substrate in the ceramic filter, it is necessary to use a catalyst slurry with a smaller particle size than the pores and a lower viscosity to ensure the uniform distribution of the catalyst on the substrate, thereby ensuring the performance of the catalyst.
[0071] In a third aspect, the present invention further provides a use of a ceramic filter tube, which includes using the ceramic filter tube as described in the first aspect or the ceramic filter tube prepared by the preparation method as described in the second aspect for dust removal and denitrification treatment and / or removal of non-methane total hydrocarbons.
[0072] It should be noted that the non-methane total hydrocarbon waste gas in the present invention refers to all volatile hydrocarbons except methane, mainly including alkanes, olefins, aromatic hydrocarbons and oxygen-containing hydrocarbons.
[0073] Compared with the prior art, the present invention has the following beneficial effects:
[0074] The ceramic filter tube provided by the present invention uses foamed nickel as a supporting skeleton, and the ceramic filter tube matrix is integrally formed on the double-side surfaces of the foamed nickel supporting skeleton. Under the premise of ensuring the original performance of the ceramic filter tube, the strength of the ceramic filter tube can be improved, and the incompatibility of the current reinforcement structure caused by material differences is fundamentally solved, and the problem of tube breakage caused by the separation and falling of the reinforcement structure from the ceramic filter tube is avoided, thereby improving the seismic resistance and service life of the ceramic filter tube; in addition, the foamed nickel can also be used as a secondary supplementary reinforcement carrier for the catalyst, which has the advantages of stabilizing the catalyst and further enhancing its denitrification performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0075] Figure 1 A comparison chart of the C-ring strength and denitrification performance of the ceramic filter tubes provided in Examples 1-10 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0076] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0077] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.
[0078] In the description of this application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0079] Example 1
[0080] This embodiment provides a ceramic filter tube, which includes:
[0081] A modified nickel foam supporting framework, wherein the modified nickel foam is modified by silica sol;
[0082] A ceramic fiber filter tube matrix, wherein the ceramic fiber filter tube matrix is integrally formed on the double-side surfaces of the nickel foam support frame, and the modified nickel foam support frame is located at the central axis of the tube wall of the ceramic filter tube;
[0083] A nano-vanadium-tungsten-titanium catalyst is loaded in the pores of the ceramic fiber filter tube matrix and in the foam nickel support skeleton.
[0084] The preparation method of the ceramic filter tube is as follows:
[0085] (1) A nickel foam (thickness of 5 mm, pore size of 6 mm, porosity of 96%) mesh is folded into a cylindrical shape with a diameter d equal to the difference between the outer diameter D of the filter tube and half of the wall thickness t (i.e., d = D-1 / 2t), and after welding, it is cleaned with a 0.5 mol / L baking soda solution and then with deionized water, and then placed in a 2 mol / L hydrochloric acid solution at room temperature for 10 min, and then cleaned with deionized water; after water washing, the nickel foam mesh is immersed in a 1 mol / L aluminum nitrate solution containing 5 wt% (the amount of silica sol added is 5 wt% of the weight of aluminum nitrate) silica sol, dried at 100°C for 6 h, and calcined at 400°C for 5 h to obtain a modified nickel foam;
[0086] (2) placing the modified nickel foam in a vacuum filtration molding device, adjusting and fixing the position of the nickel foam, injecting aluminum silicate fiber ceramic fiber filter tube matrix slurry into the filtration molding device, and obtaining a ceramic filter tube wet embryo with a modified nickel foam support skeleton by vacuum negative pressure molding; drying the composite wet embryo to obtain a composite structure;
[0087] (3) A 9wt% nano-vanadium tungsten titanium denitration catalyst slurry is quantitatively coated on the inner surface of the composite structure (the average particle size of the catalyst slurry is 85nm, the viscosity is 5.3mPa.s, the solid content is 7.2wt%, and the weight of the catalyst is 9wt% of the weight of the ceramic filter tube). The slurry enters the pores of the tube wall of the ceramic filter tube and is dried to obtain the ceramic filter tube.
[0088] Example 2
[0089] This embodiment provides a ceramic filter tube, which includes:
[0090] A modified nickel foam supporting framework, wherein the modified nickel foam is modified by silica sol;
[0091] A ceramic fiber filter tube matrix, wherein the ceramic fiber filter tube matrix is integrally formed on both side surfaces of the nickel foam support frame;
[0092] Taking the central axis of the tube wall of the ceramic filter tube as the x-axis, along the direction perpendicular to the x-axis, the distance a between the position of the nickel foam support frame and the x-axis is 1 / 10t, wherein the wall thickness of the tube wall is t;
[0093] A nano-vanadium-tungsten-titanium catalyst is loaded in the pores of the ceramic fiber filter tube matrix and in the foam nickel support skeleton.
[0094] The preparation method of the ceramic filter tube is as follows:
[0095] (1) A nickel foam (thickness of 2 mm, pore size of 3 mm, porosity of 90%) mesh is folded into a cylindrical shape with a diameter d equal to the difference between the outer diameter of the filter tube and half of the wall thickness of the filter tube, and after welding, it is cleaned with a 1 mol / L baking soda solution and then with deionized water, and then placed in a 5 mol / L sulfuric acid solution at room temperature for 10 min, and then cleaned with deionized water; after water washing, the nickel foam mesh is immersed in a 2 mol / L aluminum nitrate solution containing 10 wt% (the amount of silica sol added is 10 wt% of the weight of aluminum nitrate) silica sol, dried at 100°C for 6 h, and calcined at 300°C for 6 h to obtain a modified nickel foam;
[0096] (2) placing the modified nickel foam in a vacuum filtration molding device, adjusting and fixing the position of the nickel foam, injecting aluminum silicate fiber ceramic fiber filter tube matrix slurry into the filtration molding device, and obtaining a ceramic filter tube wet embryo with a modified nickel foam support skeleton by vacuum negative pressure molding; drying the composite wet embryo to obtain a composite structure;
[0097] (3) A nano-vanadium tungsten titanium denitration catalyst slurry (the average particle size of the catalyst slurry is 85 nm, the viscosity is 5.3 mPa.s, and the solid content is 7.2 wt%) is quantitatively coated on the inner surface of the composite structure at 9 wt%. The slurry enters the pores of the tube wall of the ceramic filter tube and is dried to obtain the ceramic filter tube.
[0098] Example 3
[0099] This embodiment provides a ceramic filter tube, which includes:
[0100] A modified nickel foam supporting framework, wherein the modified nickel foam is modified by silica sol;
[0101] A ceramic fiber filter tube matrix, wherein the ceramic fiber filter tube matrix is integrally formed on the double-side surfaces of the nickel foam support frame, and the modified nickel foam support frame is located at the central axis of the tube wall of the ceramic filter tube;
[0102] A nano-vanadium-tungsten-titanium catalyst is loaded in the pores of the ceramic fiber filter tube matrix and in the foam nickel support skeleton.
[0103] The preparation method of the ceramic filter tube is as follows:
[0104] (1) A nickel foam (3 mm thick, 3.8 mm pore size, 93.5% porosity) mesh is folded into a cylindrical shape with a diameter d equal to the difference between the outer diameter of the filter tube and half the wall thickness of the filter tube, and after welding, it is washed with a 0.5 mol / L baking soda solution and then washed with deionized water, and then placed in a 2 mol / L hydrochloric acid solution at room temperature for 10 min, and then washed with deionized water; after washing, the nickel foam mesh is immersed in a 1 mol / L aluminum nitrate solution containing 8 wt% (the amount of aluminum sol added is 8 wt% of the weight of aluminum nitrate) aluminum sol, dried at 100°C for 6 h, and calcined at 950°C for 5 h to obtain a modified nickel foam;
[0105] (2) placing the modified nickel foam in a vacuum filtration molding device, adjusting and fixing the position of the nickel foam, injecting aluminum silicate fiber ceramic fiber filter tube matrix slurry into the filtration molding device, and obtaining a ceramic filter tube wet embryo with a modified nickel foam support skeleton by vacuum negative pressure molding; drying the composite wet embryo to obtain a composite structure;
[0106] (3) A nano-vanadium tungsten titanium denitration catalyst slurry (the average particle size of the catalyst slurry is 85 nm, the viscosity is 5.3 mPa.s, and the solid content is 7.2 wt%) is quantitatively coated on the inner surface of the composite structure at 9 wt%. The slurry enters the pores of the tube wall of the ceramic filter tube and is dried to obtain the ceramic filter tube.
[0107] Example 4
[0108] The difference between this embodiment and embodiment 1 is that the nickel foam in this embodiment is not subjected to any modification treatment;
[0109] In the preparation method, a foamed nickel (thickness 5 mm, pore size 6 mm, porosity 96%) mesh is folded into a cylindrical shape, and after welding, it is cleaned with a 0.5 mol / L baking soda solution, and then cleaned with deionized water. After cleaning and drying, it is directly placed in a vacuum filtration molding device.
[0110] The rest of the preparation methods and parameters were the same as those in Example 1.
[0111] Example 5
[0112] The difference between this embodiment and embodiment 1 is that in step (1) of this embodiment, the etching treatment by immersion in a hydrochloric acid solution is not performed.
[0113] The rest of the preparation methods and parameters were the same as those in Example 1.
[0114] Example 6
[0115] The difference between this embodiment and embodiment 1 is that in step (1) of this embodiment, the amount of silica sol added is 3 wt % of the weight of aluminum nitrate.
[0116] The rest of the preparation methods and parameters were the same as those in Example 1.
[0117] Example 7
[0118] The difference between this embodiment and embodiment 1 is that in step (1) of this embodiment, the amount of silica sol added is 15 wt % of the weight of aluminum nitrate.
[0119] The rest of the preparation methods and parameters were the same as those in Example 1.
[0120] Example 8
[0121] The difference between this comparative example and Example 1 is that the porosity of the nickel foam in this comparative example is 85%.
[0122] The rest of the preparation methods and parameters were the same as those in Example 1.
[0123] Example 9
[0124] The difference between this comparative example and Example 1 is that the porosity of the nickel foam in this comparative example is 98%.
[0125] The rest of the preparation methods and parameters were the same as those in Example 1.
[0126] Example 10
[0127] The difference between this embodiment and embodiment 1 is that in this embodiment, the central axis of the tube wall of the ceramic filter tube is taken as the x-axis, and along the direction perpendicular to the x-axis, the distance a between the position of the nickel foam support skeleton and the x-axis is 1 / 5t, wherein the wall thickness of the tube wall is t.
[0128] The rest of the preparation methods and parameters were the same as those in Example 1.
[0129] Comparative Example 1
[0130] The difference between this comparative example and Example 1 is that the ceramic filter tube in this comparative example is a commercially available ceramic filter tube, model: TK3000, derived from the world's first brand technology of CLEAR EDGE filter tube from Germany.
[0131] Comparative Example 2
[0132] The difference between this comparative example and Example 1 is that the ceramic filter tube of this comparative example does not contain a foamed nickel support skeleton.
[0133] The rest of the preparation methods and parameters were the same as those in Example 1.
[0134] Comparative Example 3
[0135] The difference between this comparative example and Example 1 is that in this comparative example, the ceramic filter tube substrate is located on one side surface of the nickel foam support frame, that is, the nickel foam support frame is the inner wall surface of the tube wall of the ceramic filter tube.
[0136] In the preparation method, a nickel foam (thickness 5 mm, pore diameter 6 mm, porosity 96%) mesh is folded into a cylindrical shape with a diameter d equal to the inner diameter of the filter tube.
[0137] The rest of the preparation methods and parameters were the same as those in Example 1.
[0138] The ceramic filter tubes provided in Examples 1-10 and Comparative Examples 1-3 were tested for pressure difference, flexural strength, C-ring strength, apparent porosity, denitration performance and service life, wherein the denitration performance was measured by the denitration efficiency at 200°C. The service life was evaluated by testing the C-ring compressive strength and appearance after aging and spraying 10,000 times using the German VDI3926 method. The test results are shown in Table 1.
[0139] Figure 1 The comparison chart of the C ring strength and denitration performance of the ceramic filter tubes provided by Examples 1-10 and Comparative Examples 1-3 is shown. Figure 1 It can be seen that the ceramic filter tube provided by the present invention has higher strength and better denitrification performance during the denitrification process.
[0140] Table 1
[0141]
[0142] To sum up, the ceramic filter tube provided by the present invention uses nickel foam as a supporting skeleton, and the ceramic filter tube matrix is integrally formed on the double-side surfaces of the nickel foam supporting skeleton. Under the premise of ensuring the original performance of the ceramic filter tube, the strength of the ceramic filter tube can be improved, which fundamentally solves the incompatibility of the current reinforcement structure caused by material differences, avoids the problem of tube breakage caused by the separation and falling of the reinforcement structure from the ceramic filter tube, and improves the seismic resistance and service life of the ceramic filter tube; in addition, the nickel foam can also be used as a secondary supplementary reinforcement carrier for the catalyst, which has the advantages of stabilizing the catalyst and further enhancing its denitrification performance.
[0143] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A ceramic filter tube, characterized in that: The ceramic filter tube comprises: Nickel foam support frame; A ceramic filter tube matrix, wherein the ceramic filter tube matrix is integrally formed on both side surfaces of the nickel foam support frame; Catalyst, the catalyst is loaded in the pores of the ceramic filter tube matrix and in the nickel foam support skeleton.
2. The ceramic filter tube according to claim 1, characterized in that: The wall thickness of the nickel foam support skeleton is 2 to 5 mm, the pore size of the nickel foam support skeleton is 3 to 6 mm, and the porosity of the nickel foam skeleton is 90% to 96%; The nickel foam support skeleton comprises modified nickel foam, and the modified nickel foam comprises nickel foam and an inorganic binder for modifying the surface of the nickel foam, wherein the inorganic binder comprises an aluminum-containing binder and / or a silicon-containing binder.
3. The ceramic filter tube according to claim 1 or 2, characterized in that: The ceramic filter tube matrix includes a ceramic fiber filter tube matrix; Taking the central axis of the tube wall of the ceramic filter tube as the x-axis, along the direction perpendicular to the x-axis, the distance a between the position of the nickel foam support frame and the x-axis is 0 to 1 / 10t, wherein the wall thickness of the tube wall is t; The catalyst includes a denitration catalyst and / or a non-methane total hydrocarbon removal catalyst.
4. A method for preparing a ceramic filter tube according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: Compounding the ceramic filter tube matrix slurry on the surface of the nickel foam, forming, and loading the catalyst to obtain the ceramic filter tube; Wherein, the shape of the nickel foam is the shape of the ceramic filter tube.
5. The preparation method according to claim 4, characterized in that: The nickel foam includes modified nickel foam, and the preparation method of the modified nickel foam includes: The nickel foam to be modified is subjected to an etching treatment, and then immersed in a modifier solution for a modification treatment to obtain a modified nickel foam; The diameter d of the nickel foam, the diameter D of the ceramic filter tube and the wall thickness t of the ceramic filter tube satisfy: d=D-1 / 2t.
6. The preparation method according to claim 5, characterized in that: The nickel foam to be modified is cleaned and then subjected to an etching treatment after cleaning; The etching solution of the etching treatment includes an acid solution, and the concentration of the acid solution is 1 to 5 mol / L; The concentration of the modifier solution is 0.1-2 mol / L, and the modifier solution includes a salt solution containing an inorganic binder; the amount of the inorganic binder added is 5-10 wt% of the weight of the salt in the salt solution; The modification treatment includes sequentially performing a first drying and a heat treatment; the temperature of the heat treatment is 300 to 400° C., and the time of the heat treatment is 3 to 6 hours.
7. The preparation method according to claim 4, characterized in that: The molding method includes vacuum filtration molding; The formed embryo body is subjected to a second drying process.
8. The preparation method according to claim 4, characterized in that: The method of loading the catalyst includes a catalyst slurry coating method.
9. The preparation method according to claim 4, characterized in that: The preparation method comprises the following steps: The nickel foam to be modified is cleaned, and after cleaning, it is corroded in an acid solution with a concentration of 1 to 5 mol / L, and then immersed in a salt solution containing an inorganic binder with a concentration of 0.1 to 2 mol / L, first dried, and after the first drying, heat treated at 300 to 400° C. for 3 to 6 hours to obtain a modified nickel foam; Compounding the ceramic filter tube matrix slurry on the surface of the nickel foam, vacuum filtering and forming, performing a second drying process on the embryo after vacuum filtering and forming, and loading the catalyst by a catalyst slurry coating method to obtain the ceramic filter tube; Wherein, the added amount of the inorganic binder is 5-10wt% of the weight of the salt in the salt solution.
10. A use of a ceramic filter tube, characterized in that: The use includes using the ceramic filter tube as described in any one of claims 1 to 3 or the ceramic filter tube prepared by the preparation method as described in any one of claims 4 to 9 for dust removal and denitrification treatment and / or removal of non-methane total hydrocarbons.
Citation Information
Patent Citations
Catalytic ceramic filter tube and preparation method
CN105107310A
Ceramic fiber filter tube reinforcement method AND reinforced CERAMIC FIBER FILTER TUBE
CN107398133A
High-temperature flue gas filter pipe and preparation method thereof
CN112704978A
Cited By
High-performance ceramic fiber filter tube and preparation method thereof
CN121318262A